Faktor-Faktor Penyebab Risiko Wisata Bahari Berdasarkan Dinamika Fisik Pantai di Pesisir Selatan Jawa Barat - Taofiqurohman, Ankiq (Jurnal Ilmiah Pariwisata, 2021)
Beach tourism is the special interest tourism which part of marine tourism. The coastal dynamic makes activities on the beach area is a high risk of drowning. The South Coastal of West Java which faces The Indian Ocean is high of dangerous, while the beaches along the coast are marine tourism areas. The research aim is to analyze the marine tourism risk caused by coastal dynamics in The South Coastal of West Java. The method consist of survey method used purposive sampling method and assessment method used fish bone diagram. The result shows there are three main causes factors that create marine tourism risk, that is the beach physical, the facilities, and the people. The facilities and the people are the factors which can avoid the danger of beach physical. The people factor, especially tourist, is the main factor who reduce the risk of marine tourism. In addition, is required participation from the stakeholder to increase the quality and quantity of lifeguard and also the safety equipment. Keywords : Marine Tourism; Beach; Risk; Safety; The South Coastal Of West Java